Antimicrobial Effect of Alginate Impression after Treatment with Certain Disinfecting Agents - Khalaf, Hanan A. (Journal of Science in Medicine and Life, 2025)
Background: contaminated dental impressions can cross infect stone casts that have been poured against them, surface disinfection of dental impression done through spraying or immersion in chemical antimicrobial agents. Objectives: To observe the anti microbial action of different types of disinfecting agents (Hexyl tri ethyl ammonium chloride salt, Tetra butyl ammonium iodide salt, 1.2% sodium phenoxide salt, iodophor solutions, ethanol and 2- propanol ) on certain aerobic micro organisms. Materials and methods: the susceptibility of staphylococcus aureus, klebsiella and candida albicans to the selected antimicrobial disinfectant agents (0.5% of quaternary ammonium salts (Hexyl tri ethyl ammonium chloride salt ),0.5% of Tetra butyl ammonium iodide salt, 1.2% sodium phenoxide salt, iodophor solutions, ethanol and 2- propanol ) was evaluated by Agar diffusion plate method. The data was analyzed by a computerized statistical program. Results: The results showed that incorporation of alginate with 0.5% of quaternary ammonium salts, 0.5% of Tetra butyl ammonium iodide salt and 1.2% sodium phenoxide salt was found to be very effective in preventing the growth of candida albicans, also treating the alginate with iodophor solutions inhibit the growth of candida albicans and klebsiella spp.as well as treating alginate with Alcohols (ethanol, 2- propanol) showed great activity against klebsiella spp. and candida albicans. Conclusion: tested micro organisms are sensitive to the disinfectant agents [Hexyl tiethyl ammonium chloride salt, sodium phenoxide salt, Iodophor, ethanol and 2-propanol] with certain degree of variation among the species.